1996
DOI: 10.1111/j.1469-8137.1996.tb01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Response ofEriophorum vaginatumto CO2enrichment at different soil temperatures: effects on growth, root respiration and PO43−uptake kinetics

Abstract: SUMM.^RYIn a phytotron experiment, we e.\amined responses of a tussock sedge, Eriophorum vaginatum L., to changes in atmospherie CO., concentration and soil temperature. We were particularly interested in phosphorus (P) acquisition and below ground plant characteristics that regulated its uptake in response to CO., enrichment. Plants were grown at two CO., partial pressures, 35 and 70 Pa, three soil temperature regimes, 5, 15 and 25 °C and a constant ambient air temperature of 15 °C. Elevated CO., increased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Although similar results have been observed in other ecosystems (George et al 2003, Tjoelker et al 1999, contrary results have also been reported (Janssens et al 1998, Edwards & Norby 1999, BassiriRad et al 1996, making broad statements on how elevated CO 2 affects root respiration difficult to infer. However, nitrogen contents of A. dumosa and L. tridentata roots sampled from the elevated CO 2 plots at the NDFF are not significantly different from those from ambient CO 2 plots (Nowak et al unpublished data), and L. tridentata root nitrogen was also not affected in our greenhouse experiment after 10 months of CO 2 treatment (Table 4).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 34%
“…Although similar results have been observed in other ecosystems (George et al 2003, Tjoelker et al 1999, contrary results have also been reported (Janssens et al 1998, Edwards & Norby 1999, BassiriRad et al 1996, making broad statements on how elevated CO 2 affects root respiration difficult to infer. However, nitrogen contents of A. dumosa and L. tridentata roots sampled from the elevated CO 2 plots at the NDFF are not significantly different from those from ambient CO 2 plots (Nowak et al unpublished data), and L. tridentata root nitrogen was also not affected in our greenhouse experiment after 10 months of CO 2 treatment (Table 4).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 34%
“…Replenishment of carbohydrate reserves following burning or cutting of woody plants may require 1-2 years (Bell and Pate 1996;Kays and Canham 1991;Miyanishi and Kellman 1986). Since atmospheric CO 2 concentration is known to have large effects on plant carbohydrate status (Cruz et al 1997;Bassirirad et al 1996;den Hertog et al 1996;Read and Morgan 1996;Körner and Miglietta 1994), increasing levels of CO 2 may have important implications for plant responses to fire. Atmospheric CO 2 has been increasing since last century and is expected to reach twice preindustrial levels by the end of the twenty-first century (Houghton 1997).…”
Section: Introductionmentioning
confidence: 97%
“…rubens, Achnatherum hymenoides, and Pleuraphis rigida (Yoder et al, 2000). Although similar results have been observed in other ecosystems (Tjoelker et al, 1999;George et al, 2003), contrary results have also been reported (BassiriRad et al, 1996;Janssens et al, 1998;Edwards & Norby, 1999), making generalizations on how elevated CO 2 affects root respiration difficult. Nitrogen contents of A. dumosa and L. tridentata roots sampled from the elevated CO 2 plots at the NDFF are not significantly different from those from ambient CO 2 plots (R.S.…”
Section: Elevated Comentioning
confidence: 44%